Effect of Film-Forming Additive in Ionic Liquid Electrolyte on Electrochemical Performance of Si Negative-Electrode for LIBs. Issue 2 (1st January 2019) - Yamaguchi, Kazuki; Domi, Yasuhiro; Usui, Hiroyuki; Shimizu, Masahiro; Morishita, Shota; Yodoya, Shuhei; Sakata, Takuma; Sakaguchi, Hiroki
Abstract : 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide (EMI-TFSA) is one of the promising ionic liquids as electrolyte solvent to enhance the electrochemical performance of Si electrode for Li-ion batteries (LIBs) because of its low viscosity and high conductivity. However, it has low stability against reduction and its reductive decomposition product inhibits Li + insertion to electrodes, leading to poor cycling stability. To exert a potential of EMI-TFSA, we employed vinylene carbonate (VC) as film-forming additive. Si electrode exhibited very high cycling stability and rate capability in 20 vol.% VC-added EMI-TFSA-based electrolyte. In addition, by replacing TFSA anion with bis(fluorosulfonyl)amide (FSA) for Li salt and ionic liquid solvent, an excellent cycling performance and outstanding rate capability was achieved. VC cannot only fabricate a good surface film but also lower the interaction between Li + and FSA −, providing smooth desolvation of FSA − to obtain better high-rate performance. Non-flammability of the VC-added electrolytes was confirmed by fire resistance test in closed-system: no ignition was observed even at 300°C. Consequently, we found that mixture electrolyte consisted of EMI-based ionic liquid and VC, especially 1 M LiFSA/EMI-FSA with 20 vol.% VC, is a prospective candidate for simultaneously enhancing the electrochemical performance of Si electrode as well as safety of LIBs.